2020
DOI: 10.1097/gox.0000000000003371
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Plastic Surgery Consultations in the Emergency Department

Abstract: Background: Stay-at-Home (SAH) orders implemented in the United States to combat COVID-19 had a significant impact on health care delivery for patients with all conditions. In this study, we examined the effect SAH orders had on the Emergency Department (ED) consultation volume, injury patterns, and treatment of patients managed by our plastic surgery service. Methods: In Rhode Island, SAH orders were instituted from March 28, 2020, to June 30, 2020. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…Emergency referrals to St. George's decreased from 1,070 in 2019 to 692 in 2020. This significant decrease of 35.3% (p<0.01) corresponds to data in other studies 1 , 2 . There was a similar gender distribution in both years.…”
supporting
confidence: 90%
“…Emergency referrals to St. George's decreased from 1,070 in 2019 to 692 in 2020. This significant decrease of 35.3% (p<0.01) corresponds to data in other studies 1 , 2 . There was a similar gender distribution in both years.…”
supporting
confidence: 90%
“…Several studies examined hand trauma during the COVID-19 lockdown [ 8 - 14 ]. Garude et al found that there were more injuries from tools at home compared to the pre-COVID-19 cohort, which was also found by Ho et al, Paiva et al, Sugrue et al, and Fortane et al [ 8 - 10 , 12 - 13 ]. Ho et al also found that workplace and domestic violence injuries increased during the COVID-19 lockdown in Sydney, Australia [ 9 ].…”
Section: Discussionmentioning
confidence: 62%
“…The investigators attributed this decrease in the riskiness of the surgical site because the pharynx and upper digestive tract are where sick people often have the highest virus loads [ 30 ]. On the other hand, a comparative study done in the US employing a similar methodological approach found fewer emergency cases were hospitalised after a cosmetic surgery than in 2019 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%